ChatGPT: Opportunities and Challenges in the Learning Process of Arabic Language in Higher Education - Lelepary, Heppy Leunard; Rachmawati, Rima; Zani, Benny Novico; Maharjan, Kailie (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
Today there are no more people who do not know about technological developments. Everything is very sophisticated and modern. In fact, it is very easy for someone to know something through technology-based media and fast in disseminating various information. All of this is of course thanks to increasingly advanced technology. As recently appeared an application called Chat GPT. GPT Chat is an application that can respond to every question asked by respondents. Chat GPT stands for